Male Reproductive Anatomy - Wu, Wei (IntechOpen, 2022)
The male reproductive system, which is made up of the testes, scrotum, epididymis, vas deferens, seminal vesicles, prostate gland, bulbourethral gland, ejaculatory duct, urethra, and penis, functions mainly in the production, nourishment, and temporary storage of spermatozoa. Epigenetic modifications are essential to regulate normal gonadal development and spermatogenesis. The sperm epigenome is highly susceptible influence by a wide spectrum of environmental stimuli. This book focuses on the male reproductive system, discussing topics ranging from aspects of anatomy and risk factors for male infertility to clinical techniques and management of male reproductive health.